2020
DOI: 10.1007/s10567-020-00324-2
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Parental Involvement in Cognitive Behavioural Therapy for Adolescent Anxiety Disorders

Abstract: Anxiety disorders are common among adolescents and lead to poor long-term outcomes. Cognitive Behavioural Therapy (CBT) is an evidenced-based intervention for adolescent anxiety disorders, but little is known about whether and how parents should be involved. This systematic review evaluated how parents have been involved and associated treatment outcomes in studies of CBT for adolescent anxiety disorders. Electronic systematic searches were conducted in PsycINFO, Embase, CINAHL, Medline, AMED databases, to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Nevertheless, considering the findings of Bennett et al [ 16 ], parent-involved self-help interventions may be more useful than predominantly self-administered interventions; the inclusion of parental involvement alongside self-help interventions may overcome some of the aforementioned barriers to interventions while retaining young person engagement, compliance, and increasing the effectiveness of the intervention. This is in line with evidence that parent-involved multimedia and bibliotherapy interventions are as beneficial for behavioral disorders as therapist-led interventions in the long term [ 89 ] and that parent involvement within CBT interventions is effective for adolescent anxiety disorders [ 90 ]. This area of research warrants further investigation as the digital delivery of parent training could facilitate access to these interventions.…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, considering the findings of Bennett et al [ 16 ], parent-involved self-help interventions may be more useful than predominantly self-administered interventions; the inclusion of parental involvement alongside self-help interventions may overcome some of the aforementioned barriers to interventions while retaining young person engagement, compliance, and increasing the effectiveness of the intervention. This is in line with evidence that parent-involved multimedia and bibliotherapy interventions are as beneficial for behavioral disorders as therapist-led interventions in the long term [ 89 ] and that parent involvement within CBT interventions is effective for adolescent anxiety disorders [ 90 ]. This area of research warrants further investigation as the digital delivery of parent training could facilitate access to these interventions.…”
Section: Discussionsupporting
confidence: 84%
“…However, receiving professional support alongside computerized therapies might be beneficial, such that blended approaches could be optimal [ 57 ]. In addition, parental involvement in child CBT may lead to better outcomes, although evidence on their role in adolescent CBT is less conclusive [ 58 , 59 ]. Few of the studies we identified described direct parental involvement in the cCBT intervention; for those that did, the extent of parental involvement was minimal and sometimes optional.…”
Section: Discussionmentioning
confidence: 99%
“…While a recent meta-analysis was unable to determine whether parental involvement enhanced treatment outcomes for adolescent anxiety (Cardy et al, 2020), parental supervision and support has been shown to significantly improve treatment adherence in youth (Wahlund et al, 2021). In past interventions (Cardy et al, 2020), parental involvement has ranged from individual treatment sessions for parents, parental participation in adolescent sessions, or hard copy workbooks for parental completion. To our knowledge, no studies have examined parental involvement in smartphone-delivered CBT interventions for adolescents.…”
Section: Differences In Preferences Between Adolescents Parents and M...mentioning
confidence: 99%
“…However, to capitalise on the potential of digital health interventions in addressing treatment gaps, it is critical to also include those supporting adolescent care in the co-design process. For example, in-person CBT programs commonly involve parents suggesting a CBT smartphone intervention may benefit from parental involvement (Cardy et al, 2020). Furthermore, involving parents in the design of a smartphone app is particularly relevant for addressing concerns around excessive screen time and its potential negative impacts on mental health (Twenge and Campbell, 2019).…”
Section: Introductionmentioning
confidence: 99%